Heel kicking exercise rapidly improves pain and function in patients with acute lateral ankle sprain: a randomized controlled trial - Qi-Ning Qin; Xin Zhang; Ying-Feng Cai; Tian-Zhao Tian; Jian-Peng Zhou; Lin Li; Min Shi; Peng Huang; Hao-dong Liang; Jia-Hui Li; Zhan-Liang Tan; Yi-Xuan Fang; et al. (BMC Musculoskeletal Disorders)
Abstract Background Ankle sprain is one of the common traumatic injuries in daily life, and PRICE (protection, rest, ice, compression pressure bandaging, elevation of the affected limb) principle is routinely recommended at its early stage. In traditional Chinese medicine (TCM), bone-setting technique (BST) can quickly relieve ankle pain and improve walking function, but physicians require high skills and physical strength. In this study, we designed an exercise—heel kicking exercise (HKE) based on the principles and methods of BST. This study aims to observe its true efficacy and safety. Methods 68 patients (18–45 years old) with grade I and II lateral ankle sprain within 48 h were recruited from TCM hospital affiliated to Guangzhou medical university and 60 cases meeting the criteria were enrolled and randomized into control group and intervention group (30 cases separately). The patients in both groups were treated with the PRICE and ankle pump exercise, and the ones in intervention group added heel kicking exercise (HKE). The visual analogue scale (VAS) for pain, swelling degree, and American orthopedic foot & ankle society ankle-hindfoot scale (AOFAS) score before and after the intervention (within 4 W), and Karlsson score (the 26th week follow-up) were measured. Results Before treatment, there were no significant differences in VAS scores, swelling degrees and AOFAS scores between two groups. During the treatment for 4 weeks, VAS scores and swelling degrees of the patients in both groups gradually decreased, and the AOFAS score gradually increased (p < 0.01). In addition, patients in the intervention group were observed to get a quicker pain reliever, swelling subsiding, and ankle function restore than those in control group at most of time points of observation (1st d, 3rd d, 1st w, 2nd w, 4th w) (p < 0.05, p < 0.01). But there was no significant difference in Karlsson scores between two groups at the 26th week follow-up. Conclusions HKE is a method designed to provide rapid movement rehabilitation for patients with ankle sprains, which can be used as one of its basic treatments. Trial registration This study was registered in China Clinical Trial Center (NO. ChiCTR2300073709). Trial registration date: August 16th 2022.